(3efgGL GdeMOKjfs
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg bhdg (B: (3hYf YeQ QVi Gddg Yfg Cfg cGf EPG SeY UhJ Oa CfcQg EdG ai NJGf Ch YQS s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef (B" (3GdHGH GdSGHY hGdSHYhf ai Cf jMH GdQLd dCNjg eG jMH dfaSg (B" (3bhdg hai MOjK BNQ Yf GdfHi Udi Gddg Ydjg hSde bGd jHjJ Ydi dgh hCcd hTQH ajUHMhG bQOI hNfGRjQ s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3hYdi MhGTjgG HYV GdJUMjMGJs
(3hHOGNdgG HYV NQhe eceI HNW MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs